The Role of Explicit and Impelicit Memory in Stutteres - Golavizh Karimi-Javan; Reza Nili-Pour; Hossein A'shayeri; Fariba Yadegari; Masoud Karimlou (University of Social Welfare and Rehabilitation Sciences, 2007)
Objective: Stuttering is one of the most common speech disorders. However, its etiology is poorly understood, and is likely to be heterogeneous. Impairment of cognitive functions such as emotional memory and attention is one of the important factors. The aim of this research is to compare explicit and implicit memory between stutterers and normal individuals and also comparison of anxiety and depression between 2 groups. Materials & Methods: This is a case-control and analytical research.The participated individuals in this research were 30 male and female stutterers and the same number as the matched control group. The control group was matched for gender, age, education and bilingualism. The cue recall task performed to investigate explicit memory and the word stem completing task for implicit memory. The anxiety and depression of the individuals were measured by using general Hygiene Questionnaire (GHQ28) in this study. The performance of the individuals was measured based on positive and negative words in explicit and implicit memory and was compared with anxiety and depression score they obtained. Data was analyzed by using independent T-test, paired T-test, U-Man Witney and Willkaxon test. Results: The data indicated that stutterers recognized less emotionally positive words in explicit memory as compared with nonstutterers. Also, stutterers recognized more emotionally negative words as compared with emotionally positive words in explicit and implicit memory tasks (P<0/05). Additionally, stutterers showed more anxiety and depression as compared to nonstutterers. This difference was significant except for depression (P0.05). Conclusion: Taking into consideration the role of cognitive functions including emotional memory in motor speech programming and the difference in the function of positive versus negative emotional memories between stutterers and nonstutterers in this research, the role of emotional memory can be considered as an important factor in stutterers.